2007
DOI: 10.1002/bjs.5488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blood transfusion on outcome after pancreaticoduodenectomy for exocrine tumour of the pancreas

Abstract: In patients with exocrine tumours of the pancreas, blood transfusion should be avoided when possible. Preoperative risk factors can identify patients who are likely to require transfusion and would therefore benefit most from blood conservation methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 65 publications
2
76
3
Order By: Relevance
“…Law et al 17,26 also suggested that an altered immune response associated with sepsis, stress, and inflammatory responses following complications might contribute to the growth and proliferation of residual tumor cells in colorectal cancer patients. Recently, Yeh et al 27 examined survival in patients with pancreatic cancer who received blood transfusions in association with pancreaticoduodenectomy. Postoperative transfusion remained a predictor of survival that was independent of both nodal and margin status.…”
Section: Discussionmentioning
confidence: 99%
“…Law et al 17,26 also suggested that an altered immune response associated with sepsis, stress, and inflammatory responses following complications might contribute to the growth and proliferation of residual tumor cells in colorectal cancer patients. Recently, Yeh et al 27 examined survival in patients with pancreatic cancer who received blood transfusions in association with pancreaticoduodenectomy. Postoperative transfusion remained a predictor of survival that was independent of both nodal and margin status.…”
Section: Discussionmentioning
confidence: 99%
“…This is expected as multiple previous studies have demonstrated a similar association between perioperative transfusion and adverse events following PD. 18,19 Furthermore, 10.7% of the patients who experienced a major adverse event suffered from postoperative bleeding.…”
Section: Commentsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Although a direct causal mechanism has not been elucidated, blood transfusion has been shown to induce anergy, Tsuppressor cells, and clonal deletion. 8 Underlying clinical variables surrounding the need for blood transfusion likely confound patient outcomes and interpretation of results.…”
Section: Introductionmentioning
confidence: 99%